Insights into the molecular basis of gastric mucosa as a first step for using Raman microscopy in paediatrics - Bufka, Jiří; Vaňková, Lenka; Sýkora, Josef; Daumová, Magdaléna; Bouř, Petr; Schwarz, Jan (Heliyon, 2024)
Recent advances in endoscopic technology have allowed detailed observation of the gastric mucosa, including Raman microscopy and spectroscopy. To explore the possibilities for future diagnostic use, we discuss the measurements and molecular markers found in this tissue. The Raman spectra of 16 samples of antral mucosa and 16 samples of corpus gastric mucosa obtained from healthy donors were analysed. A stable protocol for measuring reproducible spectra was established. These data suggest that many biomarkers can be used for the rapid analysis of metabolic states and future investigations into the pathogenesis of gastrointestinal diseases.